(untitled) - Widdowson, H. G. (Oxford, 2003)
This is an introduction to linguistics, the study of human language. The author provides a succinct but lucid outline of the ways in which language has been defined, described, and explored, and guides readers towards further exploration of their own.
Keywords: Linguistics; Handbooks, manuals, etc